2019
DOI: 10.1021/acsami.9b11291
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Therapy Nanomaterials Boosting Transformation of Fe(III) into Fe(II) in Tumor Cells for Highly Improving Chemodynamic Therapy

Abstract: Chemodynamic therapy based on Fe 2+ -catalyzed Fenton reaction holds great promise in cancer treatment. However, low-produced hydroxyl radicals in tumor cells constitute its severe challenges because of the fact that Fe 2+ with high catalytic activity could be easily oxidized into Fe 3+ with low catalytic activity, greatly lowering Fenton reaction efficacy. Here, we codeliver CuS with the iron-containing prodrug into tumor cells. In tumor cells, the overproduced esterase could cleave the phenolic ester bond in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 41 publications
0
56
0
Order By: Relevance
“…BSA is used to regulate the size of MnS nanoparticles by tuning the ratio of BSA and Mn 2+ . Chemodynamic therapy (CDT) kills tumor cells by producing hydroxyl ions from H 2 O 2 at tumor sites [62]. It has been reported that Mn 2+ can be released by the MnO 2 shell on decomposition in the tumor microenvironment.…”
Section: Mns-bsa For Breast Cancer Treatment With Combination Therapymentioning
confidence: 99%
“…BSA is used to regulate the size of MnS nanoparticles by tuning the ratio of BSA and Mn 2+ . Chemodynamic therapy (CDT) kills tumor cells by producing hydroxyl ions from H 2 O 2 at tumor sites [62]. It has been reported that Mn 2+ can be released by the MnO 2 shell on decomposition in the tumor microenvironment.…”
Section: Mns-bsa For Breast Cancer Treatment With Combination Therapymentioning
confidence: 99%
“…Copyright 2019, WILEY‐VCH; Wang, An, Lin, et al (2020). Copyright 2020, Elsevier; Nie et al (2019). Copyright 2019, American Chemical Society)…”
Section: Design Of Nanomedicine For Ptt/cdtmentioning
confidence: 99%
“…Another strategy is to expand in terms of quantity and quality of catalytic ions harnessed for CDT in the nanomedicines. In the first instance, an ingenious nanodelivery system composed of CuS NPs, iron‐containing molecules and thermosensitive polymers was constructed (Nie et al, 2019). By irradiating NIR light, the resulting temperature enhancement due to CuS NPs achieved PTT ablation of tumors, and simultaneously triggered a phase change in thermosensitive polymers to release iron‐containing molecules.…”
Section: Design Of Nanomedicine For Ptt/cdtmentioning
confidence: 99%
“…As shown in Scheme 1, the template method is utilized to synthesize porous silica nanoparticles with CuS as core (CuS@SiO 2 ). [24][25][26][27] Water-soluble l-Arg is loaded within the cavity of SiO 2 . To solve the problem of premature releasing of l-Arg in the circulation, the PCM with wax-sealed profile are used to seal up the hole.…”
Section: Introductionmentioning
confidence: 99%